A DNA tetrahedron-based molecular computation device for the logic sensing of dual microRNAs in living cells. Issue 39 (9th April 2020) - Lin, Qing; Wang, Anmin; Liu, Shiyuan; Li, Jing; Wang, Jiaoli; Quan, Ke; Yang, Xiaohai; Huang, Jin; Wang, Kemin
Abstract : Endogenous miRNA expression patterns are specific to cell type and thus offer high prediction accuracy with regard to different cell identities compared to single miRNA analysis. Abstract : Endogenous miRNA expression patterns are specific to cell type and thus offer high prediction accuracy with regard to different cell identities compared to single miRNA analysis. The "AND" logic gate can be utilized as a DNA computation device that recognizes dual-miRNA inputs through strand hybridization activated computation cascades to produce controlled outputs. To integrate all recognition and computing modules within a single structure, a DNA tetrahedron-based molecular device was constructed for the logic sensing of dual miRNAs in living cells.